HISTORY AND OBJECTIVES OF THE POLISH LEGAL CLINICS PROGRAM - Czernicki, PhD, Filip (Актуальні проблеми правознавства, 2017)
Czernicki F.  Нistory  and  objectives of the polish legal clinics program. The legal clinics program, which was growing fast in Poland, has reached a phase in which forward thinking and consolidation of objectives became of great importance. For this very reason, at the turn of the year 2001 and 2002 the legal clinics and the people involved in the clinical movement decided to call into being the Polish Legal Clinics Foundation, which would take on the duty of strengthening the structure, and constructing a platform for cooperating and shaping the future of the clinical movement. The objectives assumed provide not only for ensuring fnancial stability of the clinical movement, but also to constitute a forum that would bring together the efforts to enhance the clinics’ position in the academic and legal community, and would search for a formula to inscribe legal clinics into the Polish legal system.At present there are 25 legal clinics established at every law school, approximately thirteen thousand people a year obtain legal assistance as a result of the work of legal clinics in Poland. Nearly 1,800 students and over 220 faculty members participate in the program every year, a majority of whom are also practicing lawyers. The recipients of these services are representatives of the weakest social groups, such as the unemployed, the homeless, pensioners, disabled people, crime victims, women in crisis, foreigners and refugees.The legal clinics program, which was growing fast in Poland (25 clinics have been established over a period of eight years), has reached a phase in which forward thinking and consolidation of objectives became of a great importance. For this very reason, at the turn of the year 2001 and 2002 the legal clinics and the people involved in the clinical movement decided to call into being the Polish Legal Clinics Foundation, which would take on the duty of strengthening the structure, and constructing a platform for cooperating and shaping the future of the clinical movement. The objectives assumed provide not only for ensuring fnancial stability of the clinical movement, but also to constitute a forum that would bring together the efforts to enhance the clinics’ position in the academic and legal community, and would search for a formula to inscribe legal clinics into the Polish legal system.